Projeto e avaliação experimental de uma estratégia baseada em análise intervalar aplicada ao projeto de estabilizador de sistemas de potência robusto implementado em um sistema de geração de 10KVA - COSTA, Cleyson Amorim (Universidade Federal do Pará, 2014)
In this paper, are presented the design methodology and the experimental test results of a power system stabilizer (PSS), implemented in a small-scale generation system of 10 kVA, located in the Control and Power System Laboratory (LACSPOT) at the Para Federal University (UFPA). The PSS design is based on a robust control strategy with emphasis on the structured parametric uncertainties, which are treated with tools of the interval analysis theory. These uncertainties are arising from the system operation point, which cause variations in the parameters of a linearized mathematical model referent on the dynamic behavior of the power electric system in the operation point. For the interval robust PSS design, are performed experimental tests with the purpose of estimating the linearized plant models parameters, representing the low damped modes dynamic of the interconnected generation system. The identification method is based on parametric identification technique based on least squares. From a set of input and output data, for each operation point, a ARX linear model is estimated with the purposed of the PSS design. Finally, a set of experimental tests is performed in the interconnected generation system, with the purpose of analyze the effectiveness of the interval robust control technique proposed to the PSS design. From the analysis of the active power deviation signal cost function at the synchronous generator terminal and the PSS control signal cost function, proves experimentally the good performance achieved by robust control technique proposed in comparison with a classic control technique.